Poverty - Minay, Rachel (Our world in crisis, 2018)
What is poverty? Is it do to with what we have compared to others around us, or is it to do with what we need to survive? This book looks at the causes and effects of extreme poverty - defined as having less than US1.90 a day to live on - and discusses how poverty is also a serious issue in the developed or industrialised world. It looks at what is what is being done to tackle extreme poverty and asks readers to think about what they can do to help those facing poverty, for example by donating to a local food bank. Age 9+